Social media in health care: Exploring its use by health-care professionals in Greece. (2nd January 2022) - Katsas, Ioannis; Apostolakis, Ioannis; Varlamis, Iraklis
ABSTRACT: The lockdown restrictions that have emerged during the COVID-19 pandemic have reshaped the way people live, work, and interact with each other. At the same time, it changed the way health-care professionals and national health-care systems around the world are fighting in this battle for public health. Social media (SoMe) have played their informational role in this fight with almost one-third of the world's population being active users of social media platforms. Contemporary health-care systems have tried to find ways to engage more actively with SoMe as Internet users are increasingly searching for health information on social media platforms. As a result, new demand-side levers arise in the health-care sector along with new opportunities and risks for the stakeholders. Our study looked into the responses of 173 health-care professionals in Greece. SoMe are here to stay and the majority of health-care professionals embrace them in their professional lives. Quality in health information and the work context of Greek health-care professionals in our cohort contribute to attitudes and perceptions of social media use in health care.